2017
DOI: 10.1108/jamr-06-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Integrated impact of highway infrastructure, labour productivity and circular material consumption on Indian manufacturing growth

Abstract: Purpose Manufacturing sector growth continues to be topical in the growth journey of Indian economy. The purpose of this paper is to present the modelling and analysis of the combined impact of three key driving sub-systems on the Indian manufacturing growth. It has provided relevant insights and recommendations for its sustainable growth. Design/methodology/approach The impact of three key driving sub-systems: quality of highway-related infrastructure, manufacturing labour productivity and circular material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, the important feedback elements have been developed indicating the reinforcing and the balancing loops. SFD utilized the Stella software (V10.0) to study the system behavior for various simulation scenarios (Ojha and Vrat, 2017). The developed model has incorporated the current realistic assumptions witnessed in the Indian weddings, which are explained later in the paper.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the important feedback elements have been developed indicating the reinforcing and the balancing loops. SFD utilized the Stella software (V10.0) to study the system behavior for various simulation scenarios (Ojha and Vrat, 2017). The developed model has incorporated the current realistic assumptions witnessed in the Indian weddings, which are explained later in the paper.…”
Section: Methodsmentioning
confidence: 99%
“…Also, it is necessary to obtain several permissions from local authorities, and sometimes they tend to push contractors and subcontractors to use their equipment, which is often obsolete [61][62][63]. Obsolete equipment is a common problem in developing countries, as the suppliers of these do not maintain proper maintenance records of the equipment [4]. Lastly, pressure from any political party (sfl = 0.800) demonstrates a socio-political scenario which plays a significant role in determining the prospects of highway construction projects, as in an attempt to please voters or satisfy the needs of their electorate, protests are staged on construction sites, affecting the execution of projects [64][65][66].…”
Section: Stakeholder and Political Constraintsmentioning
confidence: 99%
“…The highways themselves then suffer from severe maintenance issues and design errors that lead to severe time delays and cost overruns [67][68][69][70][71][72]. In the case of highway projects in developing countries, site investigation for designing pavement and facilities has been a major challenge [4]. Many times, the design is based on historical data, or a smaller number of samples are collected from the project location.…”
Section: Design Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information obtained from RTI responses revealed that land acquisition and encroachment clearance resulted in major project delay impacting overall performance. In developing countries, due to bureaucratic processes, delays in obtaining permission and clearances from local authorities negatively impact project success (Ojha and Vrat, 2017;Leigland, 2020). Lastly, researchers and practitioners have stated that delay in processing of claims of the contractor, sub-contractors and vendors also negatively influence project success (Muir Jr, 2015;Radzi et al, 2020).…”
Section: 33mentioning
confidence: 99%